The Effects of Plant-Associated Bacterial Exopolysaccharides on Plant Abiotic Stress Tolerance - Morcillo, Rafael; Manzanera, Maximino (Metabolites, 2021)
Plant growth-promoting rhizobacteria (PGPR) are beneficial soil microorganisms that can stimulate plant growth and increase tolerance to biotic and abiotic stresses. Some PGPR are capable of secreting exopolysaccharides (EPS) to protect themselves and, consequently, their plant hosts against environmental fluctuations and other abiotic stresses such as drought, salinity, or heavy metal pollution. This review focuses on the enhancement of plant abiotic stress tolerance by bacterial EPS. We provide a comprehensive summary of the mechanisms through EPS to alleviate plant abiotic stress tolerance, including salinity, drought, temperature, and heavy metal toxicity. Finally, we discuss how these abiotic stresses may affect bacterial EPS production and its role during plant-microbe interactions.